القيادة التحويلية وعلاقته بأداء العمال مؤسسة نقاوس للمصبرات نموذجا - لخذاري, جمال (University of Eloued جامعة الوادي, 2016)
هدفت هذه الدراسة الى التعرف على القيادة التحويلية بمتغيراتها الثلاثة (نوع الاشراف , بناء فريق العمل والتحفيز ) وعلاقتها بأداء العمال لدى مؤسسة نقاوس للمصبرات كما هدفت الى تحديد مدى تأثير المتغيرات الشخصية (الجنس السن المستوى التعليمي سنوات الخبرة) على استجابات العمال لعلاقة القيادة بأدائهم وقد اتبع الباحث المنهج الوصفي التحليلي، واستعان بالاستبيان كأداة للدراسة حيث تم توزيع 100 نسخة من الاستبيان واسترجع منه 80 نسخة وتم استبعاد 16 نسخة لعدم صلاحيتها للتحليل و بقيت 64 نسخة قابلة للدراسة. حيث أجري عليها التحليل الإحصائي لتحصيل البيانات الخام المكونة من اجابات عينة الدراسة كما استخدام برنامج (SPSS) لتحليل البيانات وقد توصلت الدراسة الى عدد من النتائج من اهمها - اثبتت الدراسة صحة الفرضية العامة حيث توصلت الى وجود علاقة إيجابيه ذات دلالة احصائية بين القيادة الإدارية والقيادة التحويلية بمتغيراتها (نوع الإشراف بناء فريق العمل التحفيز ) على أداء العمال . - تبين وجود علاقة طردية موجبة ذات دلالة إحصائية بين نوع الاشراف السائد (النمط التحويلي) و ارتفاع أداء العمال. - تبين وجود علاقة ايجابية ذات دلالة إحصائية بين التحفيز واداء العمال - تبين أنه لا توجد هناك فروق ذات دلالة إحصائية في اتجاهات افراد العينة في استجاباتهم حول تأثير القيادة التحويلية في اداء العمال , وذلك باختلاف المتغيرات الديموغرافية (الجنس والسن والمستوى التعليمي, سنوات الخبرة). - ارتفاع المستوى العام للأداء العمالي . This study aimed to determine the impact of the leadership with its three dimensions (leadership style, group of work, and motivation).on the staff performance in NGAOUS CONSERVES COMPANY. The study aimed also to determine the effect of the personal variables (sex, age, level of education and years of experience) on the responses of the employees regarding the leadership and its influence on the staff performance. A descriptive analytical approach was used, and to achieve the objectives of the study, the researcher designed and questioner as the basic research tool. The questioner was distributed to the study random sample that research 100 questionnaire, 80 questionnaires were returned ,16of them was non valid, only 64 questionnaires , valid for statistical analysis the data collected were analyses using the study prove the truth of the general Nypotheses and concluded the existence of a positive statistical relationship between leadership axe with its three dimensions (leadership style, group of work, motivation) and the increase level of job performance in NGAOUS CONSERVs COMPANY. The study concluded the existence of a positive statistical relationship between to the dominant leadership styles (the transformational leadership) and the increase level of job performance. The study concluded the existence of a positive statistical relationship between group of works and the increase level of job performance. The study concluded the existence of a positive statistical relationship between motivation and the increase level of job performance. It appears that there were no statistically significant differences in trends samples about their response of the leadership and its influence on the staff performance, depending on the following variable (age, sex, level of education, and the years of experience), The study also concluded that in general the level of job performance is good.
أطروحة ماجستير في علم الاجتماع تخصص المنظمات والمناجمنت
Keywords: القيادة، القيادة التحويلية ، إدارة المؤسسات ،الأداء الوظيفي; Leadership , Transformational Leadership , Enterprise Management, Functionality